Dyadic Interaction: Greater than the Sum of its Parts?. (25th June 2012) - Moore, Ginger A.; Powers, Christopher J.; Bass, Anneliese J.; Cohn, Jeffrey F.; Propper, Cathi B.; Allen, Nicholas B.; Lewinsohn, Peter M.
<x xml:space="preserve">Abstract</x> The study of dyadic interaction plays a major role in infancy research. To advance conceptually informed measurement of dyadic interaction and integration across studies, we examined factor structure of individual parents' and infants' measures and dyadic measures from face‐to‐face interactions in two samples of 6‐month‐old infants and their parents: mothers from a demographically heterogeneous sample (N = 164), and mothers and fathers (N = 156) from a Caucasian middle‐class sample. Results suggested that a) individual and dyadic measures, and parents' and infants' behaviors contribute independent information, b) measures of both valence and process are needed, c) there are context‐general and context‐specific qualities, and d) structure of dyadic interaction is more similar among mother–infant dyads from independent samples than between mother–infant and father–infant dyads within the same sample. Future research should use multiple measures incorporating valence, temporal processes, contextual influences, and behaviors of individual partners along with dyadic measures to adequately assess the quality of dyadic interaction.